Mobile Technology, Just-in-Time Learning and Gamification: Innovative Strategies for a CAUTI Education Program. - ONeill, Kate; Robb, Meigan; Kennedy, Rosemary; Bhattacharya, Andy; Dominici, Nicholas R.; Murphy, Andrew (Online Journal of Nursing Informatics)
Mobile technology deployment at the point of care (POC) is rapidly being embraced in healthcare as a means to address hospital-acquired infections and improve patient outcomes. Implementing technology-driven tools and best practices can be a challenge due to limited accessibility to clinically relevant resources, and reduced workforce engagement. To address this issue, an evidence-based practice change project was implemented in a community hospital located in New Jersey. The aims of this project were twofold: 1) increase nurses' knowledge with respect to best practices for catheter-associated urinary tract infections (CAUTI); and 2) enhance frontline staff engagement in best practices using a technology-driven platform infused with game-based learning. The project followed a multi-modal, time-series interventional design in which mobile tools were incorporated at the POC to provide targeted CAUTI education, and best practice strategies for registered nurses (n = 37) working in the intensive care and medical/surgical units. Presentations, videos, quizzes, case studies, and discussion boards were uploaded weekly onto a mobile technology platform (MTP) for eight weeks. This socio-technical frontline strategy allowed for just-in-time training (JIT) that promoted action-oriented learning. To incentivize ongoing user engagement, nurses accrued gamification reward points for completing structured online learning activities. Results demonstrated an 18.2% increase in sustained nursing knowledge retention scores (p = .02). In addition, staff rated technology uptake as very favorable at 87%-100%. Findings revealed the project increased nurses' knowledge of CAUTI best practices guidelines, promoted active staff engagement, encouraged technology use, and supported a positive change in POC practices overall.